Розвиток інструментів управління персоналом в кадровій політиці підприємств - Бала, О. І.; Тарнавський, М. І.; Бала, Р. Д. (Видавництво Львівської політехніки, 2014)
Проаналізовано чинники розвитку інструментів управління розвитком працівників. Виокремлено п’ять груп чинників та наведено взаємозв’язок чинників та учасників процесу розвитку. В основу запропонованого групування покладено загальні чинники, якості користувача коучингу та чинники впливу коуча на процес коучингової взаємодії. The article under consideration is an attempt at analyzing the tools of workers’ development management. Five groups of factors have been distinguished and their connection with the participants of the development process have been provided. Within the suggested grouping we have applied general factors, couching participant qualities and the factors of couch’s influence on the couching interrelation process. Under the conditions of economic crisis results overcoming an enterprise staff development is one of the most essential issues which managers of each national enterprise face. The development of an enterprise is a multidimensional issue and is concerned with different directions of enterprise activity where the production, technological, organizational, managerial, personnel, economic, financial, and social ones are the most essential is the most essential. Taking into account the versatility of methods and tools of staff management in their activity the issue of priority tools of factors search arises, which will make up a basis for the mechanism of the most significant development tool choice. There is no doubt that the workers are the most important factor of enterprise development that is why the authorities are supposed to supply their constant development. Under modern conditions of arousing competitiveness, unstable outer environment the workers’ development supply is an essential condition for general enterprise development. Recently, mangers of national enterprises become more interested in the application of different foreign tools of personnel development potential. One of these tools is a couching which ensures a constant development of a potential. To efficiently apply this tool it is advisable to investigate main factors which ensure the efficiency of their application and research the essence of the notion of couching development at an enterprise. Couching efficiency depends on individual personal and professional features of the couching process participants. It is worth noting that couching efficiency depends on both: a couch who conducts it and the user of it. That is why the factors of enterprise couching development will be grouped into three groups: couch’s influence factors, couching user’s influence factors and general (common) ones. The very application of all the factors together allows the couch forming a worker’s behavior in a way to ensure maximum work productivity, the analysis of one’s work results and the elimination of drawbacks. The factors influence research allows a couching user finding out limiting factors of a self-development. The development of couching on an enterprise and the process of its management is concerned with the enterprise in general and each worker as well. The development of an enterprise is practically useless without personal staff development. The process of couching development in the system of management is realized during a certain function of management fulfillment – the management of couching development and general functions application. Thereby, defining couching as a tool of potential development we have found out that to efficiently fulfill this function we need to correctly apply the factors of its development. To achieve this we have made a structure of the factors according to certain criteria and found five groups of factors. Correctly applying these factors a couch may create good conditions of couching participants’ development potential. Apart from this, the structuring of factors will allow to find out the directions according to which we should evaluate couching efficiency.
Development human resource management at enterprises
Keywords: коучинг; чинники; розвиток; методи; засоби; учасники; coaching; factors; development; methods; tools; participants